The human retinoblastoma gene is imprinted. - Deniz Kanber; Tea Berulava; Ole Ammerpohl; Diana Mitter; Julia Richter; Reiner Siebert; Bernhard Horsthemke; Dietmar Lohmann; Karin Buiting (PLoS Genetics, 2009)
Genomic imprinting is an epigenetic process leading to parent-of-origin-specific DNA methylation and gene expression. To date, approximately 60 imprinted human genes are known. Based on genome-wide methylation analysis of a patient with multiple imprinting defects, we have identified a differentially methylated CpG island in intron 2 of the retinoblastoma (RB1) gene on chromosome 13. The CpG island is part of a 5'-truncated, processed pseudogene derived from the KIAA0649 gene on chromosome 9 and corresponds to two small CpG islands in the open reading frame of the ancestral gene. It is methylated on the maternal chromosome 13 and acts as a weak promoter for an alternative RB1 transcript on the paternal chromosome 13. In four other KIAA0649 pseudogene copies, which are located on chromosome 22, the two CpG islands have deteriorated and the CpG dinucleotides are fully methylated. By analysing allelic RB1 transcript levels in blood cells, as well as in hypermethylated and 5-aza-2'-deoxycytidine-treated lymphoblastoid cells, we have found that differential methylation of the CpG island skews RB1 gene expression in favor of the maternal allele. Thus, RB1 is imprinted in the same direction as CDKN1C, which operates upstream of RB1. The imprinting of two components of the same pathway indicates that there has been strong evolutionary selection for maternal inhibition of cell proliferation.